Neurological involvement in the epidermal naevus syndrome. Issue 5 (May 1978) - McAuley, D L; Isenberg, D A; Gooddy, W
Abstract : The case of a left handed girl aged 18 years suffering from the "epidermal maevus syndrome" is described. She presented with dysphasia, transient left hemiparesis, and sensory symptoms due to an occlusion of the right internal carotid artery. Arterial occlusion, abnormal retinal vessels, and Raynaud's phenomenon have not been previously documented. The neurological complications of this syndrome are discussed. It is suggested that the arterial occlusion may have been caused by a dysplastic artery.